194k views
5 votes
Can you please solve this for me? f(x) = -3x2 + 2x - 7

1 Answer

3 votes
f(x) = 2x - 1

First, this is a special notation that does NOT mean f times x. It is a special notation that is read "f of x", and it means that you are to substitute a value of x into this formula and simplify the result to find the value of the answer. It is MUCH easier than everyone can possibly imagine.
Given
f(x) = 2x - 1
f(-3) means that you sustitute the value of -3 in place of the x value(s).
f(-3) = 2(-3) - 1
User TrinitronX
by
8.8k points